PDH Inhibition in Drosophila Ameliorates Sensory Dysfunction Induced by Vincristine Treatment in the Chemotherapy-Induced Peripheral Neuropathy Models - Harim Song; Sohee Kim; Ji Eun Han; Kyong-hwa Kang; Hyongjong Koh (Biomedicines)
Background/Objectives: Chemotherapy-induced peripheral neuropathy (CIPN) is a significant dose-limiting side effect of many effective anticancer agents, including vincristine. While CIPN adversely affects both oncological outcomes and the quality of life for cancer patients, the in vivo mechanisms behind CIPN pathology remain largely unknown, and effective treatments have yet to be developed. In this study, we established a novel Drosophila model of CIPN using vincristine to explore the molecular mechanisms underlying this condition. Methods: We assessed the impact of vincristine exposure on thermal nociception in Drosophila larvae using a programmable heat probe. Additionally, we investigated vincristine-induced mitochondrial dysfunction and dendritic abnormalities in class IV dendritic arborization (C4da) neurons with various fluorescent protein markers. Results: We found a dose-dependent increase in thermal hypersensitivity, accompanied by changes in the sensory dendrites of C4da neurons in vincristine-treated fly larvae. Moreover, vincristine significantly enhanced mitochondrial ROS production and mitophagy—a selective autophagy that targets dysfunctional mitochondria—indicating vincristine-induced mitochondrial dysfunction within C4da neurons. Surprisingly, inhibiting the pyruvate dehydrogenase complex (PDH), a key mitochondrial metabolic enzyme complex, effectively rescued the mitochondrial and sensory abnormalities caused by vincristine. Conclusions: Findings from this first Drosophila model of vincristine-induced peripheral neuropathy (VIPN) suggest that mitochondrial dysfunction plays a critical role in VIPN pathology, representing PDH as a potential target for the treatment of VIPN.